A COMPREHENSIVE ANALYSIS OF INTELLIGENT MULTI-AGENT BASED IOT SYSTEM FOR SMART ENERGY MANAGEMENT - Samra Sattar; Muhammad Sajid; Dr. Amjad Farooq; Dr. Junaid Arshad (Spectrum of Engineering Sciences, 2025)
Internet of Things (IoT) integration with Multi-Agent Systems (MAS) comes up with an elaborate energy management solution on smart homes and other connected environments. This approach provides a way of using autonomous agents which interact with IoT devices in time while consuming energy efficiently. Through energy management systems integration, users can adapt usage across devices based on their dynamic and varying needs, and be able to minimize waste and optimize their use of different devices’ consumers. Nevertheless, there are still problems associated with trust, security, standardization, and interoperability. It investigates the capability of IoT and MAS in reducing a sustainable energy consumption and comes up with a number of technological approaches for the decision making and the user interaction with the system. Furthermore, it suggests 2 current limitations within the system that require future research in order to overcome them and to increase the system’s performance, scalability and user acceptance in real world applications.